2015
DOI: 10.1371/journal.pone.0142756
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Regional Brain Atrophy Patterns Associated with Distinct Progression Rates in Alzheimer’s Disease

Abstract: We aimed to identify and characterize subtypes of Alzheimer’s disease (AD) exhibiting different patterns of regional brain atrophy on MRI using age- and gender-specific norms of regional brain volumes. AD subjects included in the Alzheimer's Disease Neuroimaging Initiative study were classified into subtypes based on standardized values (Z-scores) of hippocampal and regional cortical volumes on MRI with reference to age- and gender-specific norms obtained from 222 cognitively normal (CN) subjects. Baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

26
159
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(198 citation statements)
references
References 54 publications
26
159
7
Order By: Relevance
“…Among AD dementia patients, the cortical factor was associated with the worst baseline executive function, whereas the temporal factor was associated with the worst baseline memory. This result is consistent with previous work showing that thinning of frontoparietal cortical regions was associated with nonamnestic presentations and dysexecutive phenotypes (9) and that the "cortical atrophy-only" subtype had worse baseline executive function than the "hippocampal atrophy-only" subtype (16). Thus, our data-driven approach provides additional evidence that distinct atrophy patterns among AD patients impact different cognitive domains.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…Among AD dementia patients, the cortical factor was associated with the worst baseline executive function, whereas the temporal factor was associated with the worst baseline memory. This result is consistent with previous work showing that thinning of frontoparietal cortical regions was associated with nonamnestic presentations and dysexecutive phenotypes (9) and that the "cortical atrophy-only" subtype had worse baseline executive function than the "hippocampal atrophy-only" subtype (16). Thus, our data-driven approach provides additional evidence that distinct atrophy patterns among AD patients impact different cognitive domains.…”
supporting
confidence: 91%
“…Our analyses suggested that the cortical factor was associated with faster decline in both memory and executive function than the temporal factor at the dementia stage, which is consistent with the hippocampalsparing subtype exhibiting faster MMSE decline than the limbicpredominant subtype among AD dementia patients (3). Similarly, our finding that the cortical factor was associated with the most rapid memory and executive function decline among AD dementia patients was also consistent with the work by Byun et al (16). Among AD dementia patients, the cortical factor was associated with the worst baseline executive function, whereas the temporal factor was associated with the worst baseline memory.…”
supporting
confidence: 91%
See 3 more Smart Citations